Competitive advantage of nations - Porter, Michael E. (Macmillan Press LondonGB, 1990)
Investigates the details of competition in 100 selected industries in 10 leading nations, looking at patterns of industry success as well as comparing strategies and national policies that achieved it. Identifies stages of competitive development which entire economies advance and decline.